Fermentasi Seduhan Kopi Arabika Dengan Bakteri Lactobacillus Casei Dan Ragi Saccharomyces Cerevisiae Dan Uji Toksisitas - Nurul Afwa Yustika Sari; Sumardi; Salman; Ika Julianti Tambunan; Kanne Dachi; Siti Muliani Julianty (Yayasan Penelitian dan Inovasi Sumatera, 2021)
Coffee drinks are one of the most popular drinks for people of all ages, especially adults. But now with the addition of flavor, most people are enjoying coffee drinks.The purpose of the study was to see the effect of fermentation on the taste and aroma of brewed Arabica coffee with Lactobacillus casei and yeast Saccharomyces cerevisiae isolates with the addition of grape juice and sucrose and the level of toxicity of the fermentation of brewed Arabica coffee with the Brine Shrimp Lethality Test (BSLT).This research is experimental, namely the fermentation of brewed Arabica coffee with Lactobacillus casei and yeast Saccharomyces cerevisiae isolates with the addition of grape juice and sucrose. Fermentation was carried out for 3 days at open room temperature under anaerobic conditions. The results of the fermentation were tested for Brine Shrimp Lethality Test (BSLT), alcohol content test and organoleptic test by 15 panelists. Furthermore, the data were tested using the hedonic test of analysis of variance.The results of the variance showed that the fermentation of roasted Arabica coffee and green beans on taste obtained F count < F table 1% showed no significant difference, for aroma obtained F count > F table 1% showed there was a significant difference, to the color of the steeped fermented sample Roasted Arabica coffee obtained F count < F table 1% shows there is no real difference while in green beans obtained F count > F table 1% shows there is a significant difference.